On Butterflies and the Carpenter Bees (Xylocopa caffra): Perceived Ecological Roles and Description of Traditional Children’s Games in Mayotte (French island, Indian Ocean of East Africa) - Samuel Perichon (Ethnobiology Letters, 2024)
With over a million described species, insects are the most diverse group of animals on Earth. Insects, particularly those responsible for pollination, play a major ecological role that is often overlooked or even ignored. Indeed, apart from honeybees, many species are not recognized for the services they provide. What is more, all pollinating insects do not attract the same affection. Some, such as butterflies, enjoy a very positive image, while others are feared or hated, often because they can sting. During a semi-structured interview study (N = 35) on the island of Mayotte, we confirmed these views. On the other hand, butterflies and one species of carpenter bee were the subject of many children’s play and games, which have now been abandoned. Those who played with them in the past, and more simply enjoyed watching children play, seem to bitterly regret it.